Influence of defect distribution on the reducibility of CeO2−x nanoparticles. (15th September 2016) - Spadaro, Maria Chiara; Luches, Paola; Bertoni, Giovanni; Grillo, Vincenzo; Turner, Stuart; Van Tendeloo, Gustaaf; Valeri, Sergio; D'Addato, Sergio
Abstract: Ceria nanoparticles (NPs) are fundamental in heterogeneous catalysis because of their ability to store or release oxygen depending on the ambient conditions. Their oxygen storage capacity is strictly related to the exposed planes, crystallinity, density and distribution of defects. In this work a study of ceria NPs produced with a ligand-free, physical synthesis method is presented. The NP films were grown by a magnetron sputtering based gas aggregation source and studied by high resolution- and scanning-transmission electron microscopy and x-ray photoelectron spectroscopy. In particular, the influence of the oxidation procedure on the NP reducibility has been investigated. The different reducibility has been correlated to the exposed planes, crystallinity and density and distribution of structural defects. The results obtained in this work represent a basis to obtain cerium oxide NP with desired oxygen transport properties.